Loneliness as a Lethal Risk Factor: A Five-Year Prospective Survival Analysis of All-Cause Mortality Among Elderly Residents in Indonesian Vertical Public Housing - Dedi Sucipto; Brenda Jaleel; Aline Hafidzah; Oliva Azalia Putri (HM Publisher, 2025)
Introduction: Rapid urbanization in Indonesia has necessitated a shift from horizontal settlements (kampung) to vertical public housing (Rusunawa). While providing shelter, these environments may exacerbate